Abolition of lemniscal barrellette patterning in Prrxl1 knockout mice: Effects upon ingestive behavior. (2nd October 2015) - Bakalar, Dana; Tamaiev, Jonathan; Zeigler, H. Philip; Feinstein, Paul
Abstract: Ingestive behaviors in mice are dependent on orosensory cues transmitted via the trigeminal nerve, as confirmed by transection studies. However, these studies cannot differentiate between deficits caused by the loss of the lemniscal pathway vs. the parallel paralemniscal pathway. The paired-like homeodomain protein Prrxl1 is expressed widely in the brain and spinal cord, including the trigeminal system. A knockout of Prrxl1 abolishes somatotopic barrellette patterning in the lemniscal brainstem nucleus, but not in the parallel paralemniscal nucleus. Null animals are significantly smaller than littermates by postnatal day 5, but reach developmental landmarks at appropriate times, and survive to adulthood on liquid diet. A careful analysis of infant and adult ingestive behavior reveals subtle impairments in suckling, increases in time spent feeding and the duration of feeding bouts, feeding during inappropriate times of the day, and difficulties in the mechanics of feeding. During liquid diet feeding, null mice display abnormal behaviors including extensive use of the paws to move food into the mouth, submerging the snout in the diet, changes in licking, and also have difficulty consuming solid chow pellets. We suggest that our Prrxl1 −/− animal is a valuable model system for examining the genetic assembly and functional role of trigeminal lemniscal circuits in the normal control of eating in mammals and for understanding feeding abnormalities in humans resulting from the abnormal development of these circuits.